Use of Picture and Picture Models to Improve Student Learning Outcomes in Class III Natural Resources Theme of SD Negeri Langung - Salma, Siti; Kistian, Agus; Hadiid Thariiq, Shah Mohd (Journal of Elementary School Education, 2023)
The problem in this study is how to use picture and picture models to improve student learning outcomes on the theme of natural resources for class III SD Negeri Langung. It is carried out in two cycles, each cycle consisting of design, implementation, observation and reflection. Subjects in this study were 31 students. The results of teacher and student observations, as well as student tests were analyzed using the percentage formula. The research results obtained were (1) observing the activities of teachers and students in cycle 1 obtained an average score of 2.28 in a fairly good category. while the average test result was 69.67% with an average national achievement of 16 students or 55% and those who did not complete were 15 students or 45%. (2) Observation of teacher activity gets a score of 3, 85 in the very good category and observation of student activity in cycle II got an average score of 3.57 in the very good category. Meanwhile, the average test result was 85.8% with an average completion of 27 students or 90.68% and 4 students who did not complete or 9.32%. Based on the results of this study it can be concluded that by applying the Picture and Picture model it can improve student learning outcomes to become more active and the teacher's ability to improve better.